Effects of integrated nutrient management in early season cauliflower production and its residual effects on soil properties - Neupane, Babita; Aryal, Krishna; Chhetri, Lal Bahadur; Regmi, Shishir (Journal of Agriculture and Natural Resources, 2020)
This experiment was conducted in the farmer’s field at Khajrauta, Gadhawa-4, Dang, Nepal to evaluate the effect of integrated nutrient management on growth and yield of cauliflower as well as their residual effects on soil properties. The cauliflower variety silvercup-60 was grown under eight different treatments; T1: 50% N through RDF + 50% N through FYM; T2: 50% N through RDF + 50% N through PM; T3: 50% N through RDF + 50% N through VC, T4: 50% N through RDF + 25% N through FYM + 25% N through PM; T5: 50% N through RDF + 25% N through VC + 25% N through PM; T6: 50% N through RDF + 25% N through VC + 25% N through FYM; T7: 50% N through RDF + 25% N through VC +25% N through FYM; T8: 50% N through RDF + 50% N through FYM,VC and poultry manure. The experiment was laid out in RCB design with three replications. The result revealed that the highest plant height (36.40 cm), number of leaves (15), plant spread (31.72 cm), leaf area (526.5 cm2), curd weight (207.3g) and curd yield (12.85 t/ha) were found under 50% N through RDF +50% N through VC. The root length, root diameter and root density were better under all INM treatments as compared to 100% N through RDF. INM treatments showed lesser bulk density, lesser particle density, greater infiltration rate and greater organic matter content than application of 100% N through RDF. Soil total nitrogen was increased in all INM treatments while soil available phosphorus decreases in all treatments except 100% N trough RDF and 50% N through RDF +50% N through PM. Thus, farmers are suggested to apply 50% N through VC along with 50% N through RDF to increase cauliflower yield.